SPATIAL ANALYSIS IDENTIFICATION OF IDEAL AREAS CONSERVATION LOCATION IN TUAL CITY, MALUKU PROVINCE - Taufik Abdillah; Christian Novia N. Handayani; Dirga Daniel (Pusat Kajian Sumberdaya Pesisir dan Lautan IPB, 2017)
Tual City is the one of eleven districts / cities in Maluku Province. The city includes an archipelago town, has 66 islands divided into 3 island clusters, covering the cluster of Kur islands, Tayando Tam and Dullah. The sea area reaches 19,088 Km2, while the land area is 254.39 km2. The size of the sea in this area indicates the high utilization potential of both fisheries and tourism sector. Based on these, needed resources management the coastal and marine resources effectively, one of them by developing conservation area in coastal area and small islands. Tual City took the initiative to allocate part of its area to be reserved as a marine conservation area. The target of the formation of urban water conservation area Tual is the protection of important marine habitats consisting of coral reefs, seagrass and mangrove, sea turtle nesting beaches and connectivity larvae. This study was conducted to obtain potential locations of marine conservation areas that have high conservation value. Analysis of spatial data using Marxan analysis. This analysis was chosen because it provides the best solution for determining locations that have high conservation value. The results of the study indicate that the area of selected high frequency locations is 125,000 hectares, while 40,000 hectares and 64,000 hectares low. Selected high-frequency locations are in the cluster of Kur islands, Tayando Tam and in the waters north of Mas Island and Bair. Based on this study, the cluster of Kur and Tayando Tam islands become the recommended sites requiring the management of marine conservation areas as they are representative of all conservation targets. Keywords Marine Protected Area, Marxan, and Tual City